ANALISIS KELAYAKAN PENGEMBANGAN KAWASAN MINAPOLITAN YANG BERKELANJUTAN DI KABUPATEN SITUBONDO - Yuli Wibowo; Nita Kuswardhani; Qurrotun A’yuni (AGROINTEK, 2021)
Situbondo Regency is one of the regions designated as a pilot minapolitan area in Indonesia. This study aims to analyze the feasibility of developing a Minapolitan area in Situbondo Regency using a sustainable development perspective. The data processing method used in this research is the Mamdani fuzzy inference system. This study uses sustainable development dimensions to examine the feasibility of minapolitan area, including ecological, social, economic, and institutional aspects. Data processing aids using Matlab software. The results showed that the Minapolitan area in Situbondo Regency is feasible for a sustainable Minapolitan area. Situbondo Regency has an ecologically appropriate area and meets the requirements for developing fisheries and marine potential. The social environment in Situbondo Regency is also quite conducive to the development of the Minapolitan area, which can be seen from the community's active role in managing fishery resources. Community involvement in fisheries resource management is supported by fishermen and cultivation groups, including supporting institutions that can institutionally strengthen the presence of minapolitan in Situbondo Regency. The Minapolitan area's development is considered to provide economic benefits to both the communities around the area and the local government.